107 ReACT: Overall Survival From a Randomized Phase II Study of Rindopepimut (CDX-110) Plus Bevacizumab in Relapsed Glioblastoma. (August 2015) - Reardon, David A.; Schuster, James M.; Tran, David Dinh; Fink, Karen L.; Nabors, Louis B.; Li, Gordon; Bota, Daniela Annenelie; Lukas, Rimas Vincas; Desjardins, Annick; Ashby, Lynn Stuart; Duic, J. Paul; Mrugala, Maciej M.; et al.
Abstract : INTRODUCTION: EGFRvIII, a constitutively active EGFR deletion driver mutation, is associated with poor long-term survival in glioblastoma (GB). The investigational vaccine rindopepimut consists of a peptide sequence unique to EGFRvIII conjugated to keyhole limpet hemocyanin (KLH), delivered intradermally with granulocyte macrophage colony-stimulating factor. Three phase II studies in newly diagnosed, resected, EGFRvIII+ GB demonstrated encouraging progression-free survival (PFS), overall survival (OS), and safety profile. Compassionate-use experience suggests that rindopepimut may also provide benefit in relapsed GB, particularly with agents such as bevacizumab (BV). METHODS: In the Phase II "ReACT" study, BV-naïve patients in 1st or 2nd relapse with EGFRvIII+ GB were randomly assigned 1:1 to BV plus double-blinded injection of rindopepimut or control (KLH). End points: 6-month PFS (PFS6; primary), objective response rate (ORR), PFS, OS, and safety. RESULTS: Accrual is complete (n = 72); study follow-up continues (n = 30). Primary rindopepimut toxicity is grade 1 to 2 injection site reaction. For rindopepimut + BV vs KLH + BV (per investigator; RANO criteria): PFS6 = 27% (9/33) vs 11% (4/35) ( P = .048, 1-side χ 2 test); ORR = 24% (7/29) vs 17% (5/30). Central PFS/ORR assessment is underway. Median (95% CI) OS = 12.0 (9.7, –) vs 8.8 (6.8, 11.4) months (HR = 0.47 [0.25, 0.91]; P = .0208), with 8 vs 4 patients progression-free. OS analyses favor rindopepimut including when adjusted for various prognostic factors. Rindopepimut induced robust anti-EGFRvIII titers (1:12800-1:6553600) in 80% of patients. Rapid titer generation was associated with prolonged OS (HR = 0.47 [0.18, 1.27]; P = .128) within the rindopepimut arm, and was most frequent in patients with KPS ≥ 90 (odds ratio = 9.75; P = .007). Evaluation of humoral response quality and HLA typing vs outcome are underway. In an additional cohort of BV-exposed patients (n = 53), four patients experienced objective tumor response. CONCLUSION: These near-final data show that rindopepimut induces potent EGFRvIII-specific immune response and tumor regression, and appears to significantly prolong survival when administered with BV in patients with relapsed GB.